Assessment of apical pressures at different automated irrigant flow rates: an ex vivo study based on computational fluid dynamic analysis - Choudhari, Sahil; Teja, Kavalipurapu Venkata; Ramesh, Sindhu; Jose, Jerry; Janani, Krishnamachari; Kumar, Raja (Brazilian Dental Science, 2022)
Objective: The current study aimed at assessing the induced apical pressure at various simulated irrigant flow rates. Materials and Methods: Forty eight freshly extracted single-rooted premolars were decoronated and prepared to size 30 0.04 taper using HY-Flex CM rotary file system and were scanned using cone-beam computed tomography (CBCT). The scanned images were reconstructed to three-dimensional Computer-aided design models (CAD) and the 3D needle was also reconstructed. Finally, simulations were done by placing the 30 gauge open-ended needle 3 mm short of the working length. Results: There was a statistically significant difference (p<0.05) among the different groups compared. 1 ml/min flow rate induced the least apical pressures (p<0.05) as compared to the other types. Conclusion: 1 ml/min flow rates induced the least apical pressures when open-ended needles are used for irrigation. KEYWORDS Apical pressure; Computational fluid dynamic analysis; Flow rate; Irrigation; Root canal.